Dysplastic cervical squamous intraepithelial lesion of the uterine cervix associated with cavernous hemangioma: an uncommon association - Jamila Mu'utassim Ibrahim; Abdullahi Muhammad Ahmad; Ibrahim Danladi Muhammad; Nuhu Hassan (Pyramid Journal of Medicine, 2026)
Hemangioma of the cervix though mostly benign, can mimic other neoplastic conditions of the cervix, such as cervical cancer. They pose a diagnosis challenge due to their rarity, and are often found incidentally while investigating other conditions. This is a case report of such a finding, with a patient who presented with post menopausal vaginal bleeding, abnormal pap smear and colposcopy with biopsy revealed a cervical hemangioma and high grade squamous intra epithelial lesion.